2017
DOI: 10.1371/journal.pone.0174115
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of stromal vascular fraction and adipose stem cells from subcutaneous, preperitoneal and visceral morbidly obese human adipose tissue depots

Abstract: Background/ObjectivesThe pathological condition of obesity is accompanied by a dysfunctional adipose tissue. We postulate that subcutaneous, preperitoneal and visceral obese abdominal white adipose tissue depots could have stromal vascular fractions (SVF) with distinct composition and adipose stem cells (ASC) that would differentially account for the pathogenesis of obesity.MethodsIn order to evaluate the distribution of SVF subpopulations, samples of subcutaneous, preperitoneal and visceral adipose tissues fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(45 citation statements)
references
References 53 publications
1
42
0
Order By: Relevance
“…The capacity of the adipose tissue to expand relies on adipocyte hyperplasia and hypertrophy, which highly depends on the presence of adipogenic progenitor cells (Baptista, Silva, & Borojevic, ). However, the density of progenitor cells differ among fat depots, and their density in much higher in subcutaneous compared to visceral fat (Ong et al, ), which commonly locate in the external layer of blood vessel wall (Silva et al, ; Zimmerlin et al, ). The scarcity of progenitor cells in the visceral fat renders its preferential growth by hypertrophy, while subcutaneous fat grows preferentially by hyperplasia (Joe, Yi, Even, Vogl, & Rossi, ).…”
Section: Discussionmentioning
confidence: 99%
“…The capacity of the adipose tissue to expand relies on adipocyte hyperplasia and hypertrophy, which highly depends on the presence of adipogenic progenitor cells (Baptista, Silva, & Borojevic, ). However, the density of progenitor cells differ among fat depots, and their density in much higher in subcutaneous compared to visceral fat (Ong et al, ), which commonly locate in the external layer of blood vessel wall (Silva et al, ; Zimmerlin et al, ). The scarcity of progenitor cells in the visceral fat renders its preferential growth by hypertrophy, while subcutaneous fat grows preferentially by hyperplasia (Joe, Yi, Even, Vogl, & Rossi, ).…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with the possibility that visASCs actively contribute to increased tissue inflammation, in vitro experiments have revealed that they are more proinflammatory than those from subcutaneous adipose tissue [ 42 ]. In addition, human preadipocytes exposed to hypoxia secrete higher levels of inflammatory cytokines, and their conditioned medium causes a greater increase in the expression of intercellular adhesion molecule-1 and greater adhesion of monocytes to endothelial cells than adipocytes [ 43 ].…”
Section: Discussionmentioning
confidence: 93%
“…in all adipose compartments analyzed as follows: gonadal VAT, SAT, omental, and brown adipose tissue, in both male and female mice, 27 and mesenteric adipose tissue in males. 29 Interestingly, VAT stromal cells exhibit additional immunomodulatory properties that may directly or indirectly impact Treg biology, including a heightened secretion of pro-inflammatory cytokines (IL-6 among others) under in vitro conditions, compared with stromal cells isolated from SAT in both humans 69 and mice. 70 Despite recent characterization efforts of VAT and SAT stromal cells at the single-cell level, 27,62,71-73 a more comprehensive analysis using a standardized tissue preparation protocol that yields an accurate representation of all stromal components, as well as consensus markers to render results more comparable, would be very valuable.…”
Section: Depotmentioning
confidence: 99%